2019
DOI: 10.1128/aem.01336-19
|View full text |Cite
|
Sign up to set email alerts
|

Surface Water Microbial Community Response to the Biocide 2,2-Dibromo-3-Nitrilopropionamide, Used in Unconventional Oil and Gas Extraction

Abstract: Unconventional oil and gas activity can affect pH, total organic carbon, and microbial communities in surface water, altering their ability to respond to new environmental and/or anthropogenic perturbations. These findings demonstrate that 2,2-dibromo-3-nitrilopropionamide (DBNPA), a common hydraulic fracturing (HF) biocide, affects microbial communities differently as a consequence of past HF exposure, persisting longer in HF-impacted (HF+) waters. These findings also demonstrate that DBNPA has low efficacy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 73 publications
3
15
0
Order By: Relevance
“…The bacterial communities had different responses to the presence of DBNPA. DBNPA remained longer in the communities that had been exposed to the biocides previously, but these microbial communites were more tolerant to the biocide (16). A similar study was done with glutaraldehyde was done and they found similar results.…”
Section: Impact On Aquatic Communitiessupporting
confidence: 52%
“…The bacterial communities had different responses to the presence of DBNPA. DBNPA remained longer in the communities that had been exposed to the biocides previously, but these microbial communites were more tolerant to the biocide (16). A similar study was done with glutaraldehyde was done and they found similar results.…”
Section: Impact On Aquatic Communitiessupporting
confidence: 52%
“…We have recently showed that streams impacted by UOG spills containing glutaraldehyde are more resistant to the biocide when exposed to it again as compared to pristine streams (Campa et al, 2018). However, the resistance was biocide-specific, as DBNPA did not show enhanced resistance in the same streams compared to pristine streams (Campa et al, 2019). More studies providing clear evidence of environmental resistance and biocide-biocide and biocide-antibiotic cross resistance are needed to determine which biocides minimize health and environmental risk.…”
Section: Antimicrobial Resistance Enrichment Potential In the Environmentioning
confidence: 99%
“…Degradation of GA by the microbial community was also observed during the process. Campa and colleagues also investigated the microbial community response to 2,2-dibromo-3-nitrilopropionamide (DBNPA) following a similar workflow ( 14 ). In that study, the microbial response to DBNPA was distinct, compared with the response to GA, and a different microbial community structure resulted from the DBNPA treatment ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Campa and colleagues also investigated the microbial community response to 2,2-dibromo-3-nitrilopropionamide (DBNPA) following a similar workflow ( 14 ). In that study, the microbial response to DBNPA was distinct, compared with the response to GA, and a different microbial community structure resulted from the DBNPA treatment ( 14 ). To our knowledge, however, no studies have yet explored the relationships between biocide performance and the ecological properties of a souring microbial community during biocide treatment and after biocide failure, particularly how the ecological property changes could reflect the failure of biocides in souring control.…”
Section: Introductionmentioning
confidence: 99%